P671 Experiences of using vedolizumab in the treatment of inflammatory bowel disease in the East Midlands: a retrospective observational study. (25th January 2019) - White, J R; Din, S; Ingram, R; Foley, S; Alam, M A; Robinson, R; Francis, R; Tucker, E; Jalal, M; Elphick, D; Atallah, E; Norman, A; et al.
Abstract: Background: Randomised controlled trials have demonstrated efficacy of vedolizumab in ulcerative colitis (UC) and Crohn's disease (CD). Its use is increasing and data in the real-world setting is needed to inform future practice. Methods: A multi-centre retrospective observational study was conducted with patients initiated on vedolizumab across 7 UK hospitals between 1/11/14–30/11/16. The Health Research Authority approved the protocol (19/HRA/0008). Clinical disease activity was assessed at baseline, Week 14, 30 and 52 using the Harvey–Bradshaw Index (HBI) and partial Mayo Score (pMS). Clinical remission was defined as HBI ≤ 4 or pMS < 2 with a combined stool frequency and rectal bleeding subscore of ≤1. Clinical response was defined as ≥2 point decrease from baseline in pMS and ≥3 point decrease from baseline in HBI. The primary aim of this study was to describe corticosteroid-free and clinical remission after vedolizumab initiation. Secondary outcomes included effect on disease activity scores, biochemical markers (C-reactive protein (CRP) and faecal calprotectin (FCP), concomitant drug use, mucosal healing, surgical intervention, hospital admissions and adverse effects. Results: 192 patients were included in the final analysis: 99 CD, 88 UC and 5 IBD unclassified (grouped with CD in this analysis). Forty-five per cent of UC and 10% of CD patients were anti-TNF naïve. Immunomodulator and corticosteroid use at baseline for UC and CD was 41%, 49%, 27% and 27%, respectively. The median age at exposure was 44 (range 18–79) years; 49% male and median BMI was 25.7 (range 15.3–44.6). Median exposure to vedolizumab was 38.4 (IQR 23.6–58.9) for UC and 31.0 (IQR 21.6–52.5) weeks for CD. Corticosteroid-free remission rates for UC and CD were 46% and 45%, while clinical remission rates were 52% and 44%, respectively. Clinical response rate for UC was 49% and CD was 53%. The median time to corticosteroid-free remission for UC and CD was 17.6 (IQR 8.7–29.6) and 15.7 (IQR 6.0–21.7) weeks and clinical remission was 15.1 (IQR 7.4–24.9) and 10.1 (IQR 3.1–21.0) weeks, respectively. Time to clinical response for UC was 9.4 (IQR 5.3–16.4) and CD was 9.5 (IQR 6.1–18.2) weeks. Median disease activity scores decreased from baseline to 14 weeks: pMS 5 (IQR 0–9) vs. 3 (IQR 0–9), HBI 7(IQR 0–15) vs. 5 (IQR 1–14). CRP and FCP normalisation occurred by 52 weeks in CD and 14 weeks in UC. The overall rate of IBD-related hospital admissions per patient per year was 1.3 (0–18). Adverse events were reported in 6% of patients. Conclusions: Results in our vedolizumab patient population, predominately anti-TNF experienced, mirror other published real-world data and demonstrate very good clinical effectiveness and comparable safety profile. Takeda UK Ltd. sponsored this study.